(untitled) (Economic studies journal, 2020)
The study aimed to identify the most important economic developments of the outbreak of the new covid-19 epidemic in North African countries using the descriptive approach, and the study concluded that the spread of the epidemic has caused a decrease in global and local demand for North African countries, which means a decrease in exports, imports, income and prices, The disclosures also depend on information on the spread of the virus and health policy responses by countries as another economic basis. Therefore, any forecasts or estimates of future economic activity must be treated with extreme caution and likely to change as new information emerges.